Synthesis of gold nano-mushrooms via solvent-controlled galvanic replacement to enhance phototherapeutic efficiency. Issue 4 (12th January 2022) - Kang, Seounghun; Kwon, Namgook; Kang, Kyunglee; Ahn, Hojung; Kwon, Sunbum; Min, Dal-Hee; Jang, Hongje
Abstract : In galvanic replacement, it was found that the solvent polarity had a significant effect on the formed nanostructure. Hollow-tailed Au nano-mushrooms were synthesized under co-solvent conditions and used in effective cancer phototherapy. Abstract : In advanced galvanic replacement, variable factors such as the combination of two elements where actual redox reaction and post-synthetic structural transformation take place. Research on manufacturing distinctive nanostructures has mainly focused on the shape of the sacrificial nanotemplate, the presence or absence of additives, and the reaction temperature. Here, we have attempted to confirm the dependency on the solvent, which was considered to simply serve as a medium for a homogeneous chemical reaction to proceed by aiding the dispersion of the nanotemplate and reactants. Thus, we obtained mushroom-like Au nanoplates (mAuNPs) by comprehensive galvanic replacement reaction between solvents, additives, and adsorbents. The mAuNPs with a porous Au nanoplate head and a hollow nanotube tail structure were formed via an optimization process in a 50 v/v% solvent comprising water and ethylene glycol. As a result of confirming the galvanic replacement in co-solvent conditions, in which various types of water miscible solvents were introduced, it was revealed that the most critical factors for regulating the surface polymeric environment of the nanoplate were the relative polarity index of the co-solvent and the hydrogen bonding type. These depend on the molecular structure of the solvent. The manufactured mAuNPs exhibited excellent absorbance in the near-infrared region, and efficient photothermal (PT) conversion-mediated heat dissipation under local laser irradiation. These results confirm the viability of the gene-thermo dual-modal combinatorial cancer therapy based on the surface loading of oligonucleotides and peptides, and the PT therapeutic approach in vitro and in vivo .